Anion exchange membrane of aryl piperidine tetra-monomer copolymer with branched structure as well as preparation method and application of anion exchange membrane
By using an aryl piperidine tetramonomer copolymer with branched structure in the anion exchange membrane, the proportion of different monomers in the main chain is adjusted to synthesize a high-performance anion exchange membrane, which solves the problem of difficult balance between hydroxide ion conductivity and swelling rate in the existing membrane, and achieves a balance between high conductivity and low swelling rate, which is suitable for fuel cell applications.
Patent Information
- Application Number
- CN202411847821.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While the existing alkaline anion exchange membrane improves the hydroxide ion conductivity, the swelling rate is too high, affecting the dimensional stability and mechanical properties of the membrane.
Anion exchange membrane with excellent performance was synthesized by adjusting the ratio of tetraphenylporphyrin copper, Ar1 monomer and Ar2 monomer in the main chain using an arylpiperidine tetramonomer copolymer with branched structure. The method includes the synthesis of polymers, functionalization and film preparation, and the formation of a high-performance anion exchange membrane by catalyzing the Fuker hydroxyalkylation polymerization and quaternization reaction through superacid catalyzed reactions.
It significantly improves the hydroxide ion conductivity of the anion exchange membrane, and effectively inhibits the swelling rate of the membrane, ensures the dimensional stability and mechanical properties of the membrane, and is suitable for fuel cell applications.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alkaline anion exchange membranes, and relates to an anion exchange membrane of an aryl piperidine tetramonomer copolymer with a branched structure, a preparation method and an application thereof. Background Art
[0002] Industrial activities around the world have created a variety of products and services for mankind, but due to the continuous consumption of fossil energy, a large amount of carbon dioxide emissions have also been generated. In order to resolve the crisis and enable the sustainable development of the economy and society, it means that clean and abundant new energy sources must be found to meet human needs. In response to this problem, although clean energy such as wind energy, solar energy, hydropower and tidal energy have been put into use in large quantities, these energy sources are too dependent on geographical advantages and cannot guarantee stable energy output. At the same time, the energy density is relatively low. Hydrogen energy, as another environmentally friendly energy source, has the advantages of high energy density, high utilization rate, and convenient transportation. Therefore, it can make up for the shortcomings of traditional natural energy. In the field of hydrogen energy technology, fuel cells (FCs) can convert hydrogen energy into electrical energy in a high conversion efficiency and zero pollution form, so they are an important means of promoting hydrogen energy. Among them, anion exchange membrane fuel cells (AEMFCs) have received more extensive attention due to their ability to use non-precious metal catalysts, cheap polymer electrolyte membranes, long-term stable operation and use, and environmental friendliness.
[0003] As the core component of AEMFCs, alkaline anion exchange membrane plays a vital role in isolating the anode and cathode fuels and oxygen, and realizing the transfer of hydroxide ions. Therefore, the design and performance of anion exchange membrane directly affect the output power, durability and efficiency of AEMFCs. At present, most anion exchange membranes usually use materials such as polyetheretherketone, polyethersulfone and polyphenylene ether as the main chain of the membrane. However, Yu Seung Kim and other researchers pointed out in "Aryl ether-free polymer electrolytes for electrochemical and energy devices" that the main chain structure connected by ether bonds is easily attacked by hydroxide ions in an alkaline environment, resulting in main chain breakage and seriously affecting the ion conductivity and stability of the membrane. Therefore, Patric Jannasch and other scholars first reported a polyarylene piperidinium anion exchange membrane connected by all carbon in the article "Poly (arylene piperidinium) hydroxide ion exchange membranes: synthesis, alkaline stability, and conductivity". It has high alkali stability, but the membrane has only 89mS cm at 80℃. -1On this basis, Young Moo Lee and other scholars published a paper titled Poly(alkyl-terphenyl piperidinium) ionomers and membranes with an outstanding alkaline-membrane fuel-cell performance of 2.58W cm -1 In the article "1,2-diphenylethane was introduced into a polyarylpiperidine anion exchange membrane to increase the hydroxyl ion conductivity by increasing the ion exchange capacity of the membrane. However, the swelling rate of the membrane increased by nearly 10 times, which seriously affected the dimensional stability and mechanical properties of the membrane. Therefore, it is very important to develop anion exchange membranes with high hydroxyl ion conductivity and low swelling rate. Summary of the invention
[0004] The present invention aims to balance the hydroxide ion conductivity and swelling rate of an anion exchange membrane, so as to obtain a high-performance anion exchange membrane with optimal hydroxide ion conductivity and dimensional stability. The present invention provides a method for preparing an anion exchange membrane using an aromatic piperidine tetramonomer copolymer with a branched structure, so that the swelling of the membrane can be well suppressed, and while increasing the density of ionic groups, the ionic groups are distributed at multiple sites, promoting better formation of microscopic phase separation in the membrane to enhance the conduction of hydroxide ions. The anion exchange membrane prepared by the present invention has excellent hydroxide ion conductivity and dimensional stability, and can be well used in anion exchange membrane fuel cells.
[0005] The technical solution of the present invention:
[0006] An anion exchange membrane of an aromatic piperidine tetramonomer copolymer having a branched structure, the structural formula of which is as follows:
[0007]
[0008] Wherein, the structure of Ar1 is one of the following structures:
[0009]
[0010] The structure of Ar2 is one of the following structures:
[0011]
[0012] Among them, 0 <x≤0.4,0<y≤0.2。
[0013] A method for preparing an anion exchange membrane of an aromatic piperidine tetramonomer copolymer having a branched structure, comprising the following steps:
[0014] (1) Synthesis of a tetra-monomer polymer of aryl piperidine having a branched structure: tetraphenylporphyrin copper, Ar1 monomer, Ar2 monomer and dichloromethane are uniformly mixed, and then N-methyl-4-piperidone is added, and the mixture is placed in an ice bath, and trifluoroacetic acid and trifluoromethanesulfonic acid are gradually added dropwise, and the mixture is continuously stirred for 4 to 16 hours in an ice bath, and the obtained highly viscous solution is poured into a large amount of deionized water to precipitate, and then the mixture is washed with deionized water for multiple times until it is neutral, and finally dried to obtain a tetra-monomer polymer of aryl piperidine having a branched structure;
[0015] The molar ratio of tetraphenylporphyrin copper: Ar1 monomer: Ar2 monomer is x:y:(1-xy), 0 <x≤0.4,0<y≤0.2;
[0016] The molar ratio of the total molar number of the tetraphenylporphyrin copper, the Ar1 monomer and the Ar2 monomer to the N-methyl-4-piperidone is 1:1.1-1.3;
[0017] The ratio of N-methyl-4-piperidone to dichloromethane is 12mmol:5-8mL;
[0018] The ratio of N-methyl-4-piperidone to trifluoroacetic acid is 12mmol:1.2-1.8mL;
[0019] The ratio of N-methyl-4-piperidone to trifluoromethanesulfonic acid is 12mmol:6.4-8mL;
[0020] (2) Synthesis of functionalized polymer: Take the branched aryl piperidine tetramonomer polymer obtained in step (1) and dissolve it in dimethyl sulfoxide, then add potassium carbonate, stir evenly and drop iodomethane in a dark environment, then react at 40-45°C in a dark environment for 24-48 hours; after the reaction is completed, centrifuge to remove insoluble impurities, and precipitate the polymer in ethyl acetate, then wash it with ultrapure water several times and filter it. Finally, dry it in an oven to obtain a functionalized polymer product;
[0021] The ratio of the branched aryl piperidine tetramonomer polymer to dimethyl sulfoxide is 1 g: 20-25 mL;
[0022] The molar ratio of the branched aryl piperidine tetramonomer polymer to potassium carbonate is 1:2 to 2.5;
[0023] The molar ratio of the branched aryl piperidine tetramonomer polymer to methyl iodide is 1:2.5-3;
[0024] (3) Preparation of functionalized anion exchange membrane: The functionalized polymer prepared in step (2) is dissolved in dimethyl sulfoxide at room temperature, and the obtained casting solution is cast on a glass plate through a 0.45 μm PTFE syringe filter, and the solvent is dried at 65 to 70° C. to form a membrane; then, the membrane is removed and immersed in a 1 mol / L sodium hydroxide solution for 24 to 48 hours to fully perform hydroxide ion exchange, and then immersed in ultrapure water to wash away excess sodium hydroxide, thereby obtaining an anion exchange membrane of an aromatic piperidine tetramonomer copolymer having a branched structure;
[0025] The ratio of the functionalized polymer to dimethyl sulfoxide is 1-2 g:50 mL;
[0026] The casting solution is 0.2 g / cm 2 Pour dropwise onto a glass plate.
[0027] By regulating the ratio of tetraphenylporphyrin copper, Ar1 monomer and Ar2 monomer in the main chain, a series of aromatic piperidine tetramonomer polymers with branched structures in different ratios were first prepared. Secondly, the polymer was functionalized through quaternization reaction. Finally, the prepared anion exchange membrane was used in fuel cells.
[0028] Beneficial effects of the present invention: The present invention designs and prepares a four-monomer aryl piperidine-based anion exchange membrane with a branched structure for use in fuel cells through superacid-catalyzed Friedel-Crafts hydroxyalkylation polymerization and quaternization reaction. Although the three-monomer aryl piperidine-based anion exchange membrane with only tetraphenylporphyrin copper branching has improved dimensional stability, the conductivity is still not significantly improved; at the same time, the swelling rate of the three-monomer aryl piperidine-based anion exchange membrane based on the introduction of only the Ar1 structure is too large, which has a great impact on the membrane performance. In response to this problem, a type of four-monomer aryl piperidine-based anion exchange membrane with a branched structure is prepared by adjusting the ratio of the tetraphenylporphyrin copper part, the Ar1 monomer part and the Ar2 monomer part in the main chain. This type of membrane material can not only significantly improve the hydroxide ion conductivity but also well inhibit membrane swelling, and has broad application prospects in commercial fuel cells. DETAILED DESCRIPTION
[0029] The specific implementation of the present invention is further described below in conjunction with the technical solution.
[0030] Example 1 (x=0, y=0)
[0031] A terphenylpiperidine di-monomer anion exchange membrane, the structural formula of which is as follows:
[0032]
[0033] A method for preparing a terphenylpiperidine di-monomer anion exchange membrane is as follows:
[0034] (1) Synthesis of p-terphenylpiperidine di-monomer polymer: 2.3031 g (10 mmol) of p-terphenyl and 6 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.2448 g (11 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.2 mL of trifluoroacetic acid and 6.4 mL of trifluoromethanesulfonic acid were slowly dropped, followed by continuous stirring for 4 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and repeatedly washed until neutral. Finally, the polymer product was dried at 80 °C with a yield of 98%.
[0035] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 40 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.6986 g of potassium carbonate was added and 2.1805 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 24 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C., and the yield was 99%.
[0036] (3) Preparation of functionalized anion exchange membrane: Take 1g of the functionalized polymer prepared in step (2) of this embodiment, dissolve it in 50mL of dimethyl sulfoxide at room temperature, and after it is completely dissolved, cast the solution on a casting glass plate with an effective area of 6cm×6cm through a 0.45μm PTFE syringe filter, and dry the solvent in a 65℃ oven for 24h to form a membrane. After that, remove the membrane and soak it in 1mol / L sodium hydroxide solution for 48h to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then soak it in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0037] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 87 mS cm at 80°C. -1 , water absorption rate is 56.4%, swelling degree is 19.9%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 1.75Acm -1 Its peak power density reaches 0.71 W cm -1 .
[0038] Example 2 (x=0.1, y=0)
[0039] A branched aryl piperidine tri-monomer anion exchange membrane, the structural formula of which is as follows:
[0040]
[0041] A method for preparing a branched structure aryl piperidine tri-monomer anion exchange membrane is as follows:
[0042] (1) Synthesis of branched aromatic piperidine tri-monomer polymer: 2.0728 g (9 mmol) of p-terphenyl, 0.6763 g (1 mmol) of tetraphenylporphyrin copper and 5 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.2448 g (11 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.3 mL of trifluoroacetic acid and 6.6 mL of trifluoromethanesulfonic acid were slowly dropped, followed by continuous stirring for 6 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and repeatedly washed until neutral. Finally, the polymer product was dried at 80 °C with a yield of 97%.
[0043] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 40 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.5686 g of potassium carbonate was added and 1.9945 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 24 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 98%.
[0044] (3) Preparation of functionalized anion exchange membrane: 1.2 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 65°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0045] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 117 mS cm at 80°C. -1 , water absorption rate is 50.1%, swelling degree is 17.4%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 2.59Acm -1 Its peak power density reaches 1.21 W cm -1 .
[0046] Example 3 (x=0.2, y=0)
[0047] A branched aryl piperidine tri-monomer anion exchange membrane, the structural formula of which is as follows:
[0048]
[0049] A method for preparing a branched structure aryl piperidine tri-monomer anion exchange membrane is as follows:
[0050] (1) Synthesis of branched aromatic piperidine tri-monomer polymer: 1.8425 g (8 mmol) of p-terphenyl, 1.3525 g (2 mmol) of tetraphenylporphyrin copper and 6 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.3579 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.4 mL of trifluoroacetic acid and 7 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 10 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80 °C with a yield of 96%.
[0051] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 45 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.4666 g of potassium carbonate was added and 1.9169 g of iodomethane was added dropwise, and the mixture was reacted at 45° C. in the dark for 30 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 98%.
[0052] (3) Preparation of functionalized anion exchange membrane: 1.2 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 65°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0053] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 136 mS cm at 80°C. -1 , water absorption is 45.4%, swelling degree is 15.5%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 3.54Acm -1 Its peak power density reaches 1.55 W cm -1 .
[0054] Example 4 (x=0.3, y=0)
[0055] A branched aryl piperidine tri-monomer anion exchange membrane, the structural formula of which is as follows:
[0056]
[0057] A method for preparing a branched structure aryl piperidine tri-monomer anion exchange membrane is as follows:
[0058] (1) Synthesis of branched aromatic piperidine tri-monomer polymer: 1.6122 g (7 mmol) of p-terphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper and 7 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.3579 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.6 mL of trifluoroacetic acid and 7.5 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 12 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80 °C with a yield of 97%.
[0059] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 45 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.3843 g of potassium carbonate was added and 1.8544 g of iodomethane was added dropwise, and the mixture was reacted at 45° C. in the dark for 36 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 98%.
[0060] (3) Preparation of functionalized anion exchange membrane: 1.4 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 70°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0061] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 153 mS cm at 80°C. -1 , water absorption is 42.3%, swelling degree is 13.3%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 4.75Acm-1 Its peak power density reaches 2.13 W cm -1 .
[0062] Example 5 (x=0.4, y=0)
[0063] A branched aryl piperidine tri-monomer anion exchange membrane, the structural formula of which is as follows:
[0064]
[0065] A method for preparing a branched structure aryl piperidine tri-monomer anion exchange membrane is as follows:
[0066] (1) Synthesis of branched aromatic piperidine tri-monomer polymer: 1.3819 g (6 mmol) of p-terphenyl, 2.7051 g (4 mmol) of tetraphenylporphyrin copper and 8 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (13 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.8 mL of trifluoroacetic acid and 8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 16 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80 °C with a yield of 95%.
[0067] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.3715 g of potassium carbonate was added and 1.6903 g of iodomethane was added dropwise, and the mixture was reacted at 45° C. in the dark for 48 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 98%.
[0068] (3) Preparation of functionalized anion exchange membrane: 1.6 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in a 70°C oven for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0069] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 129 mS cm at 80°C. -1, water absorption is 45.9%, swelling degree is 15.9%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 3.05Acm -1 Its peak power density reaches 1.41 W cm -1 .
[0070] Example 6 (x=0.3, y=0.1)
[0071] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0072]
[0073] The structural formula of Ar1 monomer is:
[0074]
[0075] The structural formula of Ar2 monomer is:
[0076]
[0077] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0078] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 1.3819 g (6 mmol) of p-terphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.1843 g (1 mmol) of dithiophene and 7 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (13 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.8 mL of trifluoroacetic acid and 8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 12 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and repeatedly washed until neutral. Finally, the polymer product was dried at 80°C with a yield of 97%.
[0079] (2) Functionalization of polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.2160 g of potassium carbonate was added and 1.8732 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 48 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 98%.
[0080] (3) Preparation of functionalized anion exchange membrane: 1.5 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm × 6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in a 70°C oven for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0081] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 158 mS cm at 80°C. -1 , water absorption is 49.8%, swelling degree is 16.2%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 5.03Acm -1 Its peak power density reaches 2.31 W cm -1 .
[0082] Example 7 (x=0.3, y=0.15)
[0083] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0084]
[0085] The structural formula of Ar1 monomer is:
[0086]
[0087] The structural formula of Ar2 monomer is:
[0088]
[0089] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0090] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 1.2667 g (5.5 mmol) of p-terphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.2764 g (1.5 mmol) of dithiophene and 6 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.3579 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.6 mL of trifluoroacetic acid and 7.2 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 10 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80°C with a yield of 95%.
[0091] (2) Functionalization of polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 45 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.2222 g of potassium carbonate was added and 1.8827 g of methyl iodide was added dropwise, and the mixture was reacted at 40°C in the dark for 36 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60°C with a yield of 98%.
[0092] (3) Preparation of functionalized anion exchange membrane: 1.7 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 68°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0093] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 162 mS cm at 80°C. -1 , water absorption rate is 52.5%, swelling degree is 17.8%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 5.52Acm -1 Its peak power density reaches 2.42 W cm -1 .
[0094] Example 8 (x=0.3, y=0.2)
[0095] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0096]
[0097] The structural formula of Ar1 monomer is:
[0098]
[0099] The structural formula of Ar2 monomer is:
[0100]
[0101] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0102] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 1.1516 g (5 mmol) of p-terphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.3685 g (2 mmol) of dithiophene and 5 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.4 mL of trifluoroacetic acid and 6.8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 9 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80°C with a yield of 98%.
[0103] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.5355 g of potassium carbonate was added and 1.8923 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 30 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 95%.
[0104] (3) Preparation of functionalized anion exchange membrane: 1.8 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 65°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0105] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 166 mS cm at 80°C. -1, water absorption is 56.9%, swelling degree is 19.2%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 5.62Acm -1 Its peak power density reaches 2.44 W cm -1 .
[0106] Example 9 (x=0.3, y=0.2)
[0107] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0108]
[0109] The structural formula of Ar1 monomer is:
[0110]
[0111] The structural formula of Ar2 monomer is:
[0112]
[0113] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0114] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 1.1516 g (5 mmol) of p-terphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.4324 g (2 mmol) of methoxydiphenylphosphine and 7 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (13 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.8 mL of trifluoroacetic acid and 8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 12 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was obtained by drying at 80°C with a yield of 97%.
[0115] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.5140 g of potassium carbonate was added and 1.8658 g of methyl iodide was added dropwise, and the mixture was reacted at 40° C. in the dark for 48 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 98%.
[0116] (3) Preparation of functionalized anion exchange membrane: 1.5 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm × 6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in a 70°C oven for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0117] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 157 mS cm at 80°C. -1 , water absorption rate is 55.7%, swelling degree is 19.5%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 4.98Acm -1 Its peak power density reaches 2.21 W cm -1 .
[0118] Example 10 (x=0.3, y=0.2)
[0119] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0120]
[0121] The structural formula of Ar1 monomer is:
[0122]
[0123] The structural formula of Ar2 monomer is:
[0124]
[0125] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0126] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 1.1516 g (5 mmol) of p-terphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.3364 g (2 mmol) of dibenzofuran and 5 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.4 mL of trifluoroacetic acid and 6.8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 9 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80°C with a yield of 98%.
[0127] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.4847 g of potassium carbonate was added and 1.9059 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 30 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 95%.
[0128] (3) Preparation of functionalized anion exchange membrane: 1.8 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 65°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0129] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 161 mS cm at 80°C. -1 , water absorption is 60.2%, swelling degree is 19.6%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 5.49Acm -1 Its peak power density reaches 2.41 W cm -1 .
[0130] Example 11 (x=0.3, y=0.15)
[0131] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0132]
[0133] The structural formula of Ar1 monomer is:
[0134]
[0135] The structural formula of Ar2 monomer is:
[0136]
[0137] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0138] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 1.2667 g (5.5 mmol) of p-terphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.3125 g (1.5 mmol) of p-cyclohexane and 5 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.4 mL of trifluoroacetic acid and 6.8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 9 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was obtained by drying at 80°C with a yield of 98%.
[0139] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.4549 g of potassium carbonate was added and 1.8678 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 30 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C., and the yield was 95%.
[0140] (3) Preparation of functionalized anion exchange membrane: 1.8 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 65°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0141] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 159 mS cm at 80°C. -1, water absorption rate is 52.4%, swelling degree is 17.8%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 5.41Acm -1 Its peak power density reaches 2.38 W cm -1 .
[0142] Example 12 (x=0, y=0)
[0143] A biphenylpiperidine di-monomer anion exchange membrane, the structural formula of which is as follows:
[0144]
[0145] A method for preparing a biphenylpiperidine dimonomer anion exchange membrane is as follows:
[0146] (1) Synthesis of biphenylpiperidine di-monomer polymer: 1.5421 g (10 mmol) biphenyl and 6 mL dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.2448 g (11 mmol) N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred until uniform, and then 1.2 mL trifluoroacetic acid and 6.4 mL trifluoromethanesulfonic acid were slowly added, followed by continuous stirring for 2 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80 °C with a yield of 97%.
[0147] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 40 mL of dimethyl sulfoxide at room temperature. Subsequently, 2.2169 g of potassium carbonate was added and 3.4152 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 24 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 98%.
[0148] (3) Preparation of functionalized anion exchange membrane: Take 1g of the functionalized polymer prepared in step (2) of this embodiment, dissolve it in 50mL of dimethyl sulfoxide at room temperature, and after it is completely dissolved, cast the solution on a casting glass plate with an effective area of 6cm×6cm through a 0.45μm PTFE syringe filter, and dry the solvent in a 65℃ oven for 24h to form a membrane. After that, remove the membrane and soak it in 1mol / L sodium hydroxide solution for 48h to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then soak it in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0149] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 92 mS cm at 80°C. -1 , water absorption rate is 340%, swelling degree is 97%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 1.75Acm -1 Its peak power density reaches 0.87Wcm -1 .
[0150] Example 13 (x=0.3, y=0.2)
[0151] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0152]
[0153] The structural formula of Ar1 monomer is:
[0154]
[0155] The structural formula of Ar2 monomer is:
[0156]
[0157] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0158] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 0.7711 g (5 mmol) of biphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.3685 g (2 mmol) of dithiophene and 4 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred evenly, and then 1.3 mL of trifluoroacetic acid and 6.8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 8 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was dried at 80°C with a yield of 98%.
[0159] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.6773 g of potassium carbonate was added and 2.0671 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 30 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C., and the yield was 95%.
[0160] (3) Preparation of functionalized anion exchange membrane: 1.8 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 65°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0161] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 170 mS cm at 80°C. -1 , water absorption is 98.2%, swelling degree is 31.2%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 5.73Acm -1 Its peak power density reaches 2.47 W cm -1 .
[0162] Example 14 (x=0.3, y=0.15)
[0163] A branched aryl piperidine tetramer anion exchange membrane, the structural formula of which is as follows:
[0164]
[0165] The structural formula of Ar1 monomer is:
[0166]
[0167] The structural formula of Ar2 monomer is:
[0168]
[0169] A method for preparing a branched aryl piperidine tetramer anion exchange membrane is as follows:
[0170] (1) Synthesis of a branched aromatic piperidine tetramonomer polymer: 0.8482 g (5.5 mmol) of biphenyl, 2.0288 g (3 mmol) of tetraphenylporphyrin copper, 0.3125 g (1.5 mmol) of paracyclophane and 5 mL of dichloromethane were added to a 100 mL three-necked flask, followed by dropwise addition of 1.4711 g (12 mmol) of N-methyl-4-piperidone. Afterwards, the mixture was placed in an ice bath and mechanically stirred uniformly, and then 1.4 mL of trifluoroacetic acid and 6.8 mL of trifluoromethanesulfonic acid were slowly dropped into the mixture, followed by continuous stirring for 8.5 h in an ice bath. The resulting viscous liquid was poured into a large amount of deionized water and washed repeatedly until neutral. Finally, the polymer product was obtained by drying at 80°C with a yield of 98%.
[0171] (2) Preparation of functionalized polymer: 2 g of the polymer obtained in step (1) of this example was dissolved in 50 mL of dimethyl sulfoxide at room temperature. Subsequently, 1.6020 g of potassium carbonate was added and 2.0566 g of iodomethane was added dropwise, and the mixture was reacted at 40° C. in the dark for 30 h. After the reaction was completed, the insoluble impurities were removed by centrifugation to obtain a clear solution, which was then poured into ethyl acetate to precipitate the polymer, and then washed with ultrapure water several times. Finally, the functionalized polymer was dried in an oven at 60° C. with a yield of 95%.
[0172] (3) Preparation of functionalized anion exchange membrane: 1.8 g of the functionalized polymer prepared in step (2) of this embodiment was taken and dissolved in 50 mL of dimethyl sulfoxide at room temperature. After being completely dissolved, the solution was cast on a casting glass plate with an effective area of 6 cm×6 cm through a 0.45 μm PTFE syringe filter, and the solvent was dried in an oven at 65°C for 24 hours to form a membrane. After that, the membrane was removed and immersed in a 1 mol / L sodium hydroxide solution for 48 hours to completely exchange it into an anion exchange membrane in the form of hydroxide ions, and then immersed in ultrapure water to remove excess sodium hydroxide to obtain a functionalized anion exchange membrane material;
[0173] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 163 mS cm at 80°C. -1 , water absorption rate is 89.4%, swelling degree is 29.7%. In the fuel cell test, at 80℃, 1.3bar back pressure, at a current density of 5.62Acm -1 Its peak power density reaches 2.44 W cm -1 .
[0174] The above results confirm that the tetramer anion exchange membrane containing branched aryl piperidine can significantly improve the ion conductivity and well inhibit the membrane swelling by strengthening the microphase separation structure and multi-site distribution of ionic groups. In addition, although the swelling of the membrane material is increased compared with the trimer anion exchange membrane containing branched aryl piperidine, it only increases by about 1.3 to 1.5 times, and the swelling rate is still lower than that of the dimer anion exchange membrane based on terphenyl or biphenyl piperidine. Therefore, the swelling rate will not affect the dimensional stability and mechanical properties of the membrane at all, and can also have a good gain effect in fuel cell performance.
[0175] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An anion exchange membrane of an arylpiperidine tetramonomer copolymer having a branched structure, characterized in that: The structural formula of the anion exchange membrane is as follows: Wherein, the structure of Ar1 is one of the following structures: The structure of Ar2 is one of the following structures: Among them, 0 <x≤0.4,0<y≤0.2。 2. A method for preparing an anion exchange membrane of an aromatic piperidine tetramonomer copolymer having a branched structure, characterized in that: Here are the steps: (1) Synthesis of a tetra-monomer polymer of aryl piperidine having a branched structure: tetraphenylporphyrin copper, Ar1 monomer, Ar2 monomer and dichloromethane are uniformly mixed, and then N-methyl-4-piperidone is added, and the mixture is placed in an ice bath, and trifluoroacetic acid and trifluoromethanesulfonic acid are gradually added dropwise, and the mixture is continuously stirred for 4 to 16 hours in an ice bath, and the obtained highly viscous solution is poured into a large amount of deionized water to precipitate, and then the mixture is washed with deionized water for multiple times until it is neutral, and finally dried to obtain a tetra-monomer polymer of aryl piperidine having a branched structure; (2) Synthesis of functionalized polymer: The branched aryl piperidine tetramonomer polymer obtained in step (1) is dissolved in dimethyl sulfoxide, potassium carbonate is added, iodomethane is added dropwise in a light-proof environment after uniform stirring, and then the reaction is carried out at 40 to 45° C. in a light-proof environment for 24 to 48 hours; after the reaction is completed, the insoluble impurities are removed by centrifugation, and the polymer is precipitated in ethyl acetate, and then washed with ultrapure water for multiple times and filtered; finally, the functionalized polymer product is dried in an oven; (3) Preparation of functionalized anion exchange membrane: The functionalized polymer prepared in step (2) is dissolved in dimethyl sulfoxide at room temperature, and the obtained casting solution is cast on a glass plate through a 0.45 μm PTFE syringe filter, and the solvent is dried at 65 to 70° C. to form a membrane; thereafter, the membrane is removed and immersed in a 1 mol / L sodium hydroxide solution for 24 to 48 hours to allow it to fully exchange hydroxide ions, and then immersed in ultrapure water to wash away excess sodium hydroxide, thereby obtaining an anion exchange membrane of an aromatic piperidine tetramonomer copolymer having a branched structure.
3. The preparation method according to claim 2, characterized in that: In step (1), The molar ratio of tetraphenylporphyrin copper: Ar1 monomer: Ar2 monomer is x:y:(1-xy), 0 <x≤0.4,0<y≤0.2; The molar ratio of the total molar number of the tetraphenylporphyrin copper, the Ar1 monomer and the Ar2 monomer to the N-methyl-4-piperidone is 1:1.1-1.3; The ratio of N-methyl-4-piperidone to dichloromethane is 12mmol:5-8mL; The ratio of N-methyl-4-piperidone to trifluoroacetic acid is 12mmol:1.2-1.8mL; The ratio of N-methyl-4-piperidone to trifluoromethanesulfonic acid is 12mmol:6.4-8mL.
4. The preparation method according to claim 2, characterized in that: In step (2), The ratio of the branched aryl piperidine tetramonomer polymer to dimethyl sulfoxide is 1 g: 20-25 mL; The molar ratio of the branched aryl piperidine tetramonomer polymer to potassium carbonate is 1:2 to 2.5; The molar ratio of the branched aromatic piperidine tetramonomer polymer to iodomethane is 1:2.5-3.
5. The preparation method according to claim 2, characterized in that: In step (3), The ratio of the functionalized polymer to dimethyl sulfoxide is 1-2 g:50 mL; The casting solution is 0.2 g / cm 2 Pour dropwise onto a glass plate.
6. The anion exchange membrane according to claim 1 is used in a fuel cell.
Citation Information
Patent Citations
Branched poly (aryl piperidinium) anion exchange membrane as well as preparation method and application thereof
CN115678073A
Dibenzofuran-containing polyaryl piperidine anion exchange membrane and preparation method thereof
CN116622042A
Anion exchange membrane with branched structure as well as preparation method and application of anion exchange membrane
CN117467121A
Polyaryl methyl piperidine polymer, preparation method and anion exchange membrane
CN118027323A
Novel highly durable cross-linked poly(aryl piperidinium) copolymer ionomer, anion exchange membrane, and method for manufacturing same
WO2024014848A1
Cited By
Porphyrin-based branched ionomer, preparation method thereof and application of porphyrin-based branched ionomer as binder
CN121537617A